Measurement of position accuracy of engraving in plate roller and its effect on register accuracy in roll-to-roll multi-layer printing. (21st November 2017) - Kim, Cheol; Jeon, Sung Woong; Kim, Chung Hwan
Abstract: Obtaining accurate register performance between printing layers in gravure-based roll-to-roll printing equipment is a primary research target in the field of printed electronics. A plate roller is an essential print system component that must function well to ensure register accuracy. It is very important to measure and manage engraving accuracy; however, a very precise measurement apparatus is required to measure plate roller engraving accuracy, which presents challenges even for manufacturers of printed electronics devices seeking to perform an in-house evaluation. In this paper, a method for measuring plate roller engraving accuracy that requires no equipment beyond the camera used for measurement of register error, which is generally included with the printing equipment, is proposed. To study the effect of plate roller engraving accuracy on register accuracy, register errors were estimated from engraving accuracy measurements obtained using the proposed method and compared with actual register accuracies obtained from printing experiments. Information on the eccentric motion and/or run-out of the plate roller was obtained from the measured engraving accuracies. The results demonstrate that the proposed method can measure engraving accuracy and predict the magnitude of register errors prior to actual printing. It was also shown that the multi-layer printing register accuracy could not exceed the engraving accuracy of the plates themselves.